Gender‐related differences in the facial aging of Caucasian French subjects and their relations with perceived ages and tiredness. (10th May 2020) - Flament, Frederic; Belkebla, Soraya; Adam, Anne‐Sophie; Abric, Aurelie; Amar, David
Abstract: Objectives: (a) To assess and compare the changes in five facial signs with age between genders of Caucasian subjects and (b) to evaluate their links with perceived ages and tiredness. Material and Methods: Once zoomed from standardized digital photographs, five facial signs of 518 Caucasian French subjects of both genders and different ages (18‐69 years) were graded by 15 experts, using a referential Skin Aging Atlas. A large naïve panel of 1000 French subjects (500 men and 500 women) was asked to attribute a perceived age and a degree of tiredness to 200 subjects (among the 518). Results: The severity of the facial signs increases with time at a linear‐like rate. The changes in marionette lines significantly differ between genders, much more pronounced in women, and nasolabial fold was found more pronounced in men at older ages (>50 years). Before 50's, Forehead wrinkles present a slightly higher severity in men whereas at 50's women present more severe ptosis. Crow's feet wrinkles did not show significant changes. Perceived ages were found significantly correlated with the severities of the facial signs and the perception of tiredness was associated with perceived ages in men, but not in women older than 40 years. The gender‐related perceptions from the naïve panel in both perceived ages and tiredness showed a low discrepancy. Interestingly, as for changes in facial signs, the upper‐half face seems more affected for men and lower‐half face for women; after 40 years, the naïve panel seems more focusing on the same areas to predict a perceived age. Conclusion: As compared to the previous Chinese study, the present work reveals some slight ethnical‐related differences, indicating that the facial signs of the lower face play a major role in the assessment of perceived age of both genders from different ethnicity.